2019
DOI: 10.1002/ece3.5285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of landscape complexity and stand factors on arthropod communities in poplar forests

Abstract: The arthropod communities are influenced by both local conditions and features of the surrounding landscape. Landscape complexity and stand factors may both influence arthropod communities in poplar forests, but the multiscale effects of these factors on poplar defoliators and natural enemies are still poorly understood. We collected poplar arthropods at 30 sampling sites within five forest landscapes in Xinjiang, China, and assessed whether landscape complexity and stand factors influence species abundance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 60 publications
0
15
1
Order By: Relevance
“…Although we observed that insect herbivores caused more background damage in poplar stands at the nearer distance from river, our ndings contrast with previous work in that we found no clear effect of distance from river on the abundance and richness of defoliating insect herbivores (Wang et al 2019). Stone and Bacon (1995) also found that consumption of foliage by insects on the trees subjected to ooding compared to the non-ooded trees was not signi cantly different, but these results are less consistent for background herbivory itself.…”
Section: Effects Of Stand Position and Vegetation Cover On Backgroundcontrasting
confidence: 99%
See 3 more Smart Citations
“…Although we observed that insect herbivores caused more background damage in poplar stands at the nearer distance from river, our ndings contrast with previous work in that we found no clear effect of distance from river on the abundance and richness of defoliating insect herbivores (Wang et al 2019). Stone and Bacon (1995) also found that consumption of foliage by insects on the trees subjected to ooding compared to the non-ooded trees was not signi cantly different, but these results are less consistent for background herbivory itself.…”
Section: Effects Of Stand Position and Vegetation Cover On Backgroundcontrasting
confidence: 99%
“…And we can rule out the direct effects of human actions, because a variety of methods and tools (e.g. chemical or biological insecticides) that are widely used for pest control in agriculture are not available or are not suitable for application in forestry (Wang et al 2019). However, forestry operations could affect defoliation intensity of phytophagous insects in a number of indirect ways (Wesołowski and Rowiński 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The variables related to the stand characteristics, topographical characteristics, and soil properties of sample plots were treated as stand-level variables (Mezei et al, 2014). In addition, through remote sensing imagery of Gaofen-2 (China Centre for Resources Satellite Data and Application, 2020) and eld investigation, the forest coverage of the buffer with a radius of 1000 m around the sample plots ranges from 10% to 75% to ensure a reasonable distribution of the landscape-level variables (Wang et al, 2019).…”
Section: Area In the Middle Stage Of Rtb Outbreakmentioning
confidence: 99%